Inactivation of the biological activities of the thermostable direct hemolysin of Vibrio parahaemolyticus by ganglioside Gt1. - Takeda, Y (1976)
Biological activities of the thermostable direct hemolysin produced by Vibrio parahaemolyticus, such as its hemolytic activity and lethal activity, were inhibited by neuraminidase-sensitive gangliosides, of which GT1 ganglioside was the most inhibitory. Neuraminidase-resistant gangliosides did not affect the activities of the hemolysin. Results showed that horse erythrocytes, which are resistant to the hemolysin, do not contain the neuraminidase-sensitive gangliosides GT1 and GD1a. Therefore, we propose that neuraminidase-sensitive gangliosides, and especially GT1 ganglioside, may be the receptor sites on the membranes for the thermostable direct hemolysin of V. parahaemolyticus.